Effects of intensive nutrition education and counseling on nutritional status of pregnant women in East Shoa Zone, Ethiopia - Wakwoya, Ermias Bekele; Belachew, Tefera; Girma, Tsinuel (Frontiers in Nutrition, 2023)
Background Nutritional status is defined as an individual’s health condition as it is influenced by the intake and utilization of nutrients. Maternal malnutrition is widespread throughout the world, with Sub-Saharan Africa and Asia bearing the brunt of the burden. The objective of this study was to evaluate the effect of intensive nutrition education and counseling on nutritional status during pregnancy. Methods and materials The study was a one-year, two-arm parallel design cluster randomized controlled trial conducted in the East Shoa zone, Ethiopia, from January 1, 2021, to February 30, 2022. A total of 374 participants were enrolled in the intervention (n = 185) and control (n = 189) groups. End-line data were collected from 163 women, from each group. The intervention package provided three counseling sessions by trained midwives, three-page take-home brochures prepared in local languages, and the delivery of 18 weekly serial short text messages. The women in the control group received routine nutrition education from the health facilities. After adjusting for potential confounders, a linear mixed-effects model was employed to assess the intervention effect. Results After the intervention, the mean mid-upper arm circumference in the intervention group increased by 1.8% (23.08 vs. 23.44, p < 0.01). Similarly, the proportion of undernutrition in the intervention group was 11% (25 vs. 36%, p = 0.02) lower compared to the control arm. At the end of the trial, women in the intervention arm had significantly better nutritional status than women in the control group (β = 0.47, p < 0.01). Conclusion The findings showed that intensive nutrition education and counseling using the health belief model was effective in improving nutritional status and reducing undernutrition among pregnant women. As a result, nutrition education and counseling using HBM constructs, as well as regular reminder messages, should be provided to pregnant women as part of the routine antenatal care service.